Karakteristik Kimia dan Organoleptik Crackers Dengan Substitusi Tepung Beras Merah dan Tepung Tempe - Selawati, Fitri; Quddus, Ati Atul; ., Mardiana (Universitas Muhammadiyah Semarang, 2024)
The use of brown rice flour and tempeh flour in making crackers is intended to reduce the use of wheat flour and utilize local food ingredients by processing them into flour whose nutritional content is very good for the health of the human body. The aim of this research was to determine the effect of substitution of brown rice flour and tempeh flour on chemical and organoleptic characteristics and to determine the best formulation of crackers with substitution of brown rice flour and tempeh flour based on chemical and organoleptic characteristics. This research used a Completely Randomized Design (CRD) method with 3 treatment levels and 3 replications. The treatments carried out included P1 (90% brown rice flour; 10% tempeh flour), P2 (80% brown rice flour; 20% tempeh flour) and P3 (70% brown rice flour; 30% tempeh flour). Based on the results of research that has been carried out, making crackers with the substitution of brown rice flour and tempeh flour has a significant effect on chemical and organoleptic characteristics such as water content, ash content, fat content, protein content, carbohydrate content, taste attributes, texture attributes, and other attributes. does not have a significant effect on color and aroma attributes. The best treatment for brown rice flour crackers and tempeh flour was in the P3 treatment with chemical and organoleptic characteristics including air content 3.85%, ash content 1.54%, fat content 24.56%, protein content 14.57%, carbohydrate content 60 .80%, color attribute 5.04 (somewhat like), aroma attribute 4.76 (somewhat like), taste attribute 4.92 (somewhat like), texture attribute 4.88 (somewhat like) and overall 4.84 (somewhat Like).